Hypoxia-Inducible Factor-1α Target Genes Contribute to Retinal Neuroprotection - Cheng, Lin; Yu, Honghua; Yan, Naihong; Lai, Kunbei; Xiang, Mengqing (Frontiers in Cellular Neuroscience, 2017)
Hypoxia-inducible factor (HIF) is a transcription factor that facilitates cellular adaptation to hypoxia and ischemia. Long-standing evidence suggests that one isotype of HIF, HIF-1α, is involved in the pathogenesis of various solid tumors and cardiac diseases. However, the role of HIF-1α in retina remains poorly understood. HIF-1α has been recognized as neuroprotective in cerebral ischemia in the past two decades. Additionally, an increasing number of studies has shown that HIF-1α and its target genes contribute to retinal neuroprotection. This review will focus on recent advances in the studies of HIF-1α and its target genes that contribute to retinal neuroprotection. A thorough understanding of the function of HIF-1α and its target genes may lead to identification of novel therapeutic targets for treating degenerative retinal diseases including glaucoma, age-related macular degeneration, diabetic retinopathy, and retinal vein occlusions.